Bruce Lee’s Combat in a Nutshell: an analysis of the strategic contributions of his edited works (Revista de Artes Marciales Asiáticas, 2024)
This research examines Bruce Lee’s martial arts philosophy, with a particular focus on his unique approach to jeet kune do, to address the scientific rigour gap in the analysis of his martial arts methodology. The study adopts a case study research strategy and employs content analysis using MaxQDA v.11 software. A selection of Lee’s official literature, prioritising unchanged writings and those reflecting his direct thought, forms the research sample. The key findings highlight Lee’s development of five ways of attacking, demonstrating an intricate knowledge of timing, distance, and rhythm. His emphasis on adaptability in combat emphasises the dynamic interplay between offensive and defensive manoeuvres. Lee’s preference for parrying over blocking, his focus on evasion, and strategic concepts such as seven stars and three fronts emphasise the importance of protecting vital body areas. In summary, Bruce Lee’s martial arts philosophy is characterised by adaptability, strategic decision-making, and efficient technique execution. His approach, constantly evolving and rejecting preconceived combat outcomes, is underpinned by principles of simplicity, economy, fluidity, and spontaneity. This comprehensive system integrates both offensive and defensive strategies, reflecting his commitment to refining the martial arts into a practical and responsive discipline.